2016
DOI: 10.1590/1982-0216201618113915
|View full text |Cite
|
Sign up to set email alerts
|

Potenciais evocados auditivos de tronco encefálico em fumantes

Abstract: Purpose: to perform a comparative study of brainstem evoked auditory potentials between smokers and non-smokers. Methods: the group studied was composed of 40 individuals, being 20 non-smokers and 20 smokers within the range of 20 to 59 years of age. All participants had to present responses to tonal thresholds within normal range and tympanometry type A, with the presence of ipsilateral and contralateral acoustic reflexes. Both groups underwent brain stem auditory evoked potential (BAEP). The parameters used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…This article analyzes the scientific production concerning the effect of tobacco use in the peripheral auditory system and / or central nervous system; as various studies have hypothesized that cigarette smoking can cause hearing loss 1,[4][5][6][7][8][11][12][13][14][15][16][17][18][19][20] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…This article analyzes the scientific production concerning the effect of tobacco use in the peripheral auditory system and / or central nervous system; as various studies have hypothesized that cigarette smoking can cause hearing loss 1,[4][5][6][7][8][11][12][13][14][15][16][17][18][19][20] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review showed that all the publications found correspond to health and were published in magazines related to speech therapy 5,12,18 otolaryngology 4,13-15 diagnostics, 16 biomedicine, and medicine 17,19 . All articles had audiological diagnostics of smokers as a principal theme.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations